Effect of Single Parenting on Children’s Social Welfare in Chahi Sub-County Kisoro District. - Nyiraneza, Gloria (Kabale University, 2024)
The study assessed the effect of single parenting on children’s social welfare in chahi sub-county Kisoro district. The objectives of the study were to assess the effect of single parenting on children's access to education in Chahi Sub-County, to assess the impact of single-parent families on household income in Chahi Sub-County, and to propose interventions to support single-parent households in Chahi Sub-County. The study adopted a descriptive research design across a sample of 80 respondents who were selected from the Chahi sub-county Kisoro district. Data collection tools were interviews and questionnaires. The results of the study revealed that female respondents were highly represented in the study. The results of the study further revealed that single-parent families contribute to children's social well-being by providing psychosocial support and education to children. The study concluded that single-parent families in Chahi Sub-County face significant economic and educational challenges. Financial instability, unemployment, and poverty are prevalent, which directly impact children’s access to education and overall well-being. The economic strain leads to inadequate educational resources, poor housing conditions, and malnutrition, which in turn affect children’s academic performance and psychological well-being. Current interventions, such as financial support policies, community donations, and medical services, play a crucial role in addressing immediate needs. However, these interventions are often not sufficient on their own. While financial support helps alleviate some of the financial burdens, and medical services contribute to better health, there is a clear need for more comprehensive and sustainable support systems. Notably, universal pre-kindergarten programs and policies aimed at enhancing employment opportunities are identified as particularly effective in providing long-term benefits. The study concluded that the government should expand and increase financial assistance to provide more comprehensive support and there should be a combination of community donations with long-term support programs to ensure sustained assistance.